Answer:
x = 6
Explanation:
1/2(8x+4)-1/3(3x+9)=17 can be calculated as:
Firstly, simplify 1/2(8x+4) to become (1*8x+4)/2 = (8x+4)/2
Secondly, factor out the common term 4:
(8x+4)/2 = 4(2x+1)/2
Now we got the equation:
4(2x+1)/2 - 1/3(3x+9)=17
After this, we see that 4(2x+1)/2 can be simplify to:
2(2x+1)
Thirdly, simplify 1/3(3x+9) = 1*(3x+9)/ 3 = (3x+9) / 3
Factor out the common term 3:
= 3(x+3)/3
Now we got the equation:
2(2x+1) - 3(x+3)/3 = 17
Cancel 3, we got:
2(2x+1) - (x+3) = 17
Break the brackets:
4x+2 - x - 3 = 17
4x - x - 3 + 2 = 17
3x - 1 = 17
Add 1 to both side:
3x - 1 + 1 = 17 + 1
3x - 0 = 18
3x = 18
Divide both side by 3:
3x /3 = 18/3
1x = 6
x = 6
Hope this help you :3